Ensuring sustainable celebrations - Ong, Hwai Chyuan *; Long, Chiau Ming *; Gew, Lai Ti * (Star Media Group Berhad, 2025)
The festivals of Chinese New Year, Thaipusam , and Hari Raya will be observed in the coming months. With future generations in mind, we must optimise the opportunity to enjoy celebrations while also taking care of the planet.